Pulsed laser deposition of epitaxial yttrium iron garnet films with low Gilbert damping and bulk-like magnetization - M. C. Onbasli; A. Kehlberger; D. H. Kim; G. Jakob; M. Kläui; A. V. Chumak; B. Hillebrands; C. A. Ross (APL Materials, 2014)
Yttrium iron garnet (YIG, Y 3Fe5O12) films have been epitaxially grown on Gadolinium Gallium Garnet (GGG, Gd3Ga5O12) substrates with (100) orientation using pulsed laser deposition. The films were single-phase, epitaxial with the GGG substrate, and the root-mean-square surface roughness varied between 0.14 nm and 0.2 nm. Films with thicknesses ranging from 17 to 200 nm exhibited low coercivity (<2 Oe), near-bulk room temperature saturation moments (∼135 emu cm−3), in-plane easy axis, and damping parameters as low as 2.2 × 10−4. These high quality YIG thin films are useful in the investigation of the origins of novel magnetic phenomena and magnetization dynamics.